Pengaruh Komunikasi Orangtua terhadap Pola Perilaku Anak Kelas XI IPA di SMA Futuhiyyah Mranggen - Tsabita Maharani; Tri Suyati; Venty Venty (Departement of Mathematics Education, 2023)
Research on the Effect of Parental Communication on the Behavior Patterns of Class XI Children in SMA Futuhiyyah Mranggen, aims to get an overview of how parental communication affects children's behavior patterns at home and at school. To obtain information about the behavior of students in the school environment, and to find out how much influence parental communication has on children's behavior patterns at school. This research is a correlational descriptive quantitative research. The population of this research data is 150 students. The sample in this study was 127 students who were taken by simple random sampling technique. The effect of parental communication on behavior patterns in SMA Futuhiyyah Mranggen is -146.228 <0.05, then Ho is accepted and Ha is rejected, so it can be said that there is no influence of parental communication on children's behavior patterns. This means that parental communication with children's behavior patterns at SMA Futuhiyyah Mranggen has no impact on children's behavior patterns. In general, this study was able to determine the importance of the influence of parental communication on children's behavior patterns so that it can be used as a reference for providing counseling services in order to improve parental communication and the behavior patterns of children that influence it.